2016
DOI: 10.1016/j.ynstr.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Biological and psychological predictors of posttraumatic stress disorder onset and chronicity. A one-year prospective study

Abstract: BackgroundFew studies have prospectively examined risk factors for posttraumatic stress disorder (PTSD) in the aftermath of a traumatic exposure. The aim of this study is to identify the concurrent influence of psychological and biological diatheses on PTSD onset and maintenance, taking into account socio-demographic factors and psychiatric antecedents.MethodsA total of 123 civilians (61.8% of women) recruited in emergency units, were assessed using validated instruments during the first week and then at 1, 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 65 publications
3
20
0
Order By: Relevance
“…In maltreatment samples, diurnal salivary cortisol levels were positively related to PTSS when trauma occurred within a year of sampling and negatively correlated when trauma was more distal (Weems and Carrion, 2007). Nonintentional injury studies examining multiple analytes obtained acutely have generally found positive correlation of 12-hour urinary cortisol, norepinephrine and/or epinephrine concentrations with later developing PTSS in children and adults (Delahanty et al, 2005; Gandubert et al, 2016). In particular, the divergence of plasma noradrenaline and cortisol level across the first 6-months in youth who developed PTSD points to alteration across interacting HPA and ANS stress response systems (Pervanidou et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In maltreatment samples, diurnal salivary cortisol levels were positively related to PTSS when trauma occurred within a year of sampling and negatively correlated when trauma was more distal (Weems and Carrion, 2007). Nonintentional injury studies examining multiple analytes obtained acutely have generally found positive correlation of 12-hour urinary cortisol, norepinephrine and/or epinephrine concentrations with later developing PTSS in children and adults (Delahanty et al, 2005; Gandubert et al, 2016). In particular, the divergence of plasma noradrenaline and cortisol level across the first 6-months in youth who developed PTSD points to alteration across interacting HPA and ANS stress response systems (Pervanidou et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although cortisol levels tended to normalize over time, basal plasma noradrenaline was elevated at 1 month and increased further at 6 months after the injury (Pervanidou et al, 2007). Similarly, in adults, PTSS 4 to 6 months after injury were predicted by higher norepinephrine and lower cortisol obtained from 12-hour overnight urinary samples (Gandubert et al, 2016) and low morning and elevated afternoon salivary cortisol sampled 2 days after hospitalization (McFarlane et al, 2011). Evidence to date suggests that alteration in stress responsive systems occurs within the first several days following injury exposure and predicts PTSS during the first year.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work suggests that post-traumatic symptomatology is influenced by peri-traumatic responses. [13][14][15] Evidence suggests a substantial proportion of individuals who immobilize peritraumatically experience TI in response to post-traumatic reminders. 16 Several authors suggest that exposure to traumatic reminders may re-instantiate the original cascade of defensive stages, resulting in post-traumatic symptomology.…”
Section: Introductionmentioning
confidence: 99%
“…These studies found that the impact of violent loss and the unexpectedness of the loss on PTSD severity was fully mediated by peritraumatic distress and dissociation; peritraumatic helplessness and PD emerged as unique mediators. Prospective studies of women found peritraumatic distress predictive of acute PTSD, defined as one month after the traumatic event, whereas PD predicted mid-term PTSD at four months posttrauma (Gandubert et al, 2016; Johnson, Pike, & Chard, 2001). These studies also found that, in adult female CSA victims, PD was the only variable found to significantly predict symptom severity across symptom type or disorder.…”
mentioning
confidence: 99%